EVALUATION COMPETENCE OF A UNIVERSITY TEACHER: CONTENTAND PURPOSES - Tat’yana E. Isaeva (Высшее образование в России, 2016)
The article proves the necessity of singling out the evaluation competence in the structure of the university teacher’s professional culture. The significance of this competence has enhanced lately due to the requirement of working@out the assessment funds, aimed at identifying the levels of students’ competencies and conducting evaluation procedures of students’ achievements assessment. The author considers the evaluation competence to be the key teacher’s competence as it finally defines his pedagogical culture. This competence characterizes teacher’s acquaintance withassessment methods for measuring students’ learning outcomes, his ability to master technologies for stimulating students to further progress in learning. The evaluation competence includes five units: knowledge, technology, reflexion, development and assessment.